The vasodilating effect of glucose differs among vessels at different branching level in the porcine retina ex vivo. (February 2019) - Jensen, Peter Skov; Aalkjaer, Christian; Bek, Toke
Abstract: Diabetic retinopathy is characterized by retinal lesions related to disturbances in retinal blood flow. The metabolic dysregulation in diabetes involves hyperglycemia which in both clinical and experimental studies has been shown to induce dilatation of larger retinal vessels, which has been suggested to be mediated by nitric oxide (NO). However, the effects of glucose on the diameter of smaller retinal vessels that are the site of development of diabetic retinopathy are unknown. Diameter changes in porcine retinal arterioles, pre-capillary arterioles and capillaries were studied ex vivo during acute changes in intraluminal glucose concentrations that mimicked changes in plasma glucose in diabetic patients. The experiments were repeated during blocking of NO-synthesis. Intravascular application of 2 mM glucose dilated arterioles and capillaries significantly, while 20 mM glucose dilated precapillary arterioles significantly. Intravascular application of 20 mM glucose dilated precapillary arterioles previously exposed to 2 mM glucose, while no significant diameter changes were observed after application of 2 mM glucose in vessels previously exposed to 20 mM glucose. No diameter changes were observed after application of 5.5 mM glucose in vessels previously exposed to both 2 mM and 20 mM glucose in either order. There was no significant difference between the diameter responses in the absence and presence of NO-synthesis blocker. Glucose induced dilatation of porcine precapillary arterioles ex vivo differs from the response in larger arterioles and capillaries, and the response is unaffected by the blocking of NO-synthesis. This may have implications for understanding the pathophysiology of diseases in the retinal microcirculation, such as diabetic retinopathy. Highlights: Glucose induced dilatation of retinal vessels differs among small and large branches. The glucose induced dilatation is unaffected by blocking of nitric oxide synthesis. The findings may have implications for understanding the pathophysiology of diseases in the retinal microcirculation, such as diabetic retinopathy.